Analisis Komparatif Kinerja Keuangan dan Prediksi Kebangkrutan Perusahaan Telekomunikasi - Norman Thomas, Gen (Bina Nusantara University, 2013)
This study aims to reveal the comparative financial performance and prediction of bankruptcy in 2 (two) telecommunications services company; PT Bakrie Telecom Tbk and PT Mobile-8 Telecom.Tbk. Â Compared to other telecommunications services companies formerly established, such as PT Telkom Tbk., PT Indosat Tbk., and PT XL Axiata Tbk., PT Bakrie Telecom, Tbk. and PT Mobile-8 Telecom, Tbk. are still new and relatively untested, so it is interesting to do the research. The research method used was comparative analysis between two similar objects studies based on financial ratios. Based on calculations and ratio analysis, it shows that the ratio of liquidity to the financial condition of PT Mobile-8 Telecom Tbk is better than PT Bakrie Telecom Tbk, but leverage ratios, activity ratios, and profitability ratios happen PT Bakrie Telecom Tbk better than PT Mobile-8 Telecom Tbk. In the calculation on dupont analysis of PT Bakrie Telecom Tbk has an average ROA of 2:42%, which is better than ROA of PT Mobile-8 Telecom Tbk -12.29%. Bankruptcy prediction for PT Mobile-8 Telecom Tbk with z score much smaller, 4.81 (2007), -5.82 (2008), -7.50 (2009); it means the greater the likelihood of PT Mobile-8 Telecom Tbk towards bankruptcy. As for the PT Bakrie Telecom Tbk with a z score has narrowed, -0.11 (2007), 0.8 (2008), -2.30 (2009) but not as small as z score PT Mobile-8 Telecom Tbk, this also means that larger opportunities for PT Bakrie Telecom Tbk likely headed bankruptcy.